Observation of corrosion process of reinforcing steel - Ismail, Mohammad; Erica Dina, Erica Dina; Abdul Rahman, Rosly; Ikhsan, Sabirin (Faculty of Civil Engineering, UTM, 2005)
Corrosion of reinforcement is one of the major contributors to the deterioration of reinforced concrete structures. The cause of corrosion can be due to carbonation or chloride attack. Early detection of corrosion process can prevent costly repair or structural collapse. The aim of this study was to look at the possibility of using modified fibre optic sensor to monitor the corrosion process of reinforcing steel. The corrosion process was monitored by an unclad plastic optical fibre sensor attached to a steel bar. A fibre optic spectrometer was used to detect the spectrum of the white light. The light spectrum changes in intensity as corrosion develop and progresses on the bar surface. Three samples of mortar prisms with steel bars inserted at the centre were prepared. One sample was immersed in 10% Sodium Chloride (NaCl) solution and another in 20% NaCl. The results were compared with a reference sample. The corrosion process was observed for a 20-day period. The results show that the initial value of the outgoing light from the optical fibre was 4000 counts and reduced to less than 3600 counts after 20 days. The intensity value decreases slowly as the corrosion progresses.